Engineering biodegradable polymeric network for the efficient removal of organo‐amphiphilic toxicants. (9th January 2020) - Kumar, Rajan; Rajpoot, Anubhav; Roy, Amritangshu; Shunmugam, Raja
Abstract : Motivated with the continued demand for developing quality material showing better response for the efficient removal of organo‐amphiphilic toxicants, we have demonstrated the growth of three‐dimensional polymer organic framework—a covalent crosslinked polymer C2B derived via photon triggered thiol‐alkene click reaction. Instrumentation techniques such as nuclear magnetic resonance, thermogravimetric analysis, and fourier transform infrared spectroscopy were used for the characterization. FESEM and Cryo‐SEM analysis were done to analyze the morphology of the resin. The adsorption and release experiments were done with ultraviolet‐visible spectroscopic technique. The polymer C2B derived from polyolefin and tetrathiol via thiol‐alkene photoclick reaction showed efficiency toward adsorption of organo‐amphiphilic contaminants such as dioxane, dimethylformamide, fluorescein, and rhodamine B (RH). Even the material selectively showed the efficient release of toxicant—RH. Moreover, it can be reused over cycles. This makes the polymer C2B as potential candidate to be commercially viable for textile industries.